Upaya Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fikih Materi Perawatan Jenazah melalui Metode Demonstrasi di MA Al-Azhar Sampung - sulung timur; Tamrin Fathoni (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The demonstration method is an instructional approach that enables teachers to explain concepts and procedures by directly showing students how a task or activity is performed. This method encourages active participation, improves understanding, and helps students connect theoretical knowledge with practical application. At MA Al-Azhar, fiqh learning was previously dominated by the lecture method, which limited student engagement and made it difficult for many students to understand the learning materials. As a result, a considerable number of students failed to achieve the Minimum Completeness Criteria (KKM). The implementation of the demonstration method proved to be effective in overcoming these challenges. Through classroom action research, students’ learning outcomes showed consistent improvement in every cycle, indicating that the method had a positive impact on academic achievement. In addition to higher test scores, students became more active during the learning process by asking questions, participating in demonstrations, and interacting with both teachers and classmates. The classroom atmosphere also became more conducive because students were more focused and motivated to learn. These findings suggest that the demonstration method not only enhances cognitive learning outcomes but also fosters greater student participation and confidence. Therefore, the demonstration method can be recommended as an effective teaching strategy for fiqh subjects and other practice-oriented courses to improve the quality of teaching and learning in Islamic schools.